The effectiveness of promotional strategies by Tabung Haji to attract customers in Jasin / Salwah Abdullah - Abdullah, Salwah (Faculty of Business and Management, 2004)
Promotion is very important to many organizations. A good promotion may promise a good feedback from the customers towards the product and services offered. This project paper is to assess promotion strategies done by Tabung Haji Jasin, in Malacca. The objective of this research is to identify the effectiveness of promotional strategies by TH in promoting their product and services and to find out customer's awareness towards This products and services. Thus, recommendations are included in this project paper in order to help TH to increase the effectiveness of the promotions activities and create customers awareness towards the product and services. In getting relevant data, 60 questionnaires were distributed to the selected respondents. The respondents are customers of TH from Jasin district. Data collected were analyzed by using the Statistical Package for Social Science (SPSS) program. The analysis includes the frequency, cross tabulation, and correlation. Several limitations were faced in completing this study. The sampling size is small compared to the actual populations of TH depositors for Jasin District. Therefore, to obtain the correct sample size may required more times and effort which is beyond researcher capabilities and time frame given.